Adventures with waffles - Parr, Maria, 1981-; Puzey, Guy; Forrester, Kate (Illustrator) (Somerville, Massachusetts : Candlewick Press, 2015)
"Hardly a day passes without Trille and Lena inventing some kind of adventure that often ends in trouble. Whether it's coaxing a cow onto a boat or sledding down the steepest and iciest hill with a chicken, there is always a thrill--and sometimes an injury--to be had. Trille loves to share everything with Lena, even Auntie Granny's waffles..."--Publisher.
Translation of: Vaffelhjarte.
Elementary Grade.
720
Accelerated Reader
Accelerated Reader AR
Reading Counts RC
Keywords: Friendship -- Juvenile fiction; Secrecy -- Juvenile fiction; Friendship -- Fiction; Secrets -- Fiction; Friendship; Secrecy; Fiction; Juvenile works